Molecular genetics of bacterial pathogenesis - Miller, Virginia L (ASM Press, 1994)
This volume offers an overview of the progress in our understanding of the pathogenesis of important bacterial pathogens, and gives an insight into how these advances have been made via uses of recombinant DNA and other molecular techniques. Much of this work came from the laboratory of Dr Stanley Falkow, and all of the contributors to this book are alumni of the Falkow laboratory. Introductory chapters outline the situation when Dr Falkow and his staff first began their investigations, describe key experiments, and give a flavour of the laboratory atmosphere at the time. The 29 chapters following are topical reviews of key areas in what is one of the frontier fields of contemporary microbiology.
Keywords: genetika, lékařská genetika; bakteriologie; biologie